Case Report: Generalize Pustular Psoriasis Pregnancy (GPPP) in Multiple Pregnancies - Aida Musyarrofah; Probo Yudha Pratama Putra; Dwi Nurwulan Pravitasari; Yulia Nugrahanitya (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: General Pustular psoriasis pregnancy (GPPP) is a dermatosis that occurs in pregnancy and requires serious management to reduce the risk of mortality and morbidity in both pregnancy mother and fetus. This disorder is also called impetigo herpetiform. Case Presentation: We report a woman with multiple pregnancies, G3P2A0 at 21 weeks gestation, with well-defined erythematous macules 5–10 cm in diameter, partly coalescent, with thick scales, and 0.1–0.2 cm diameter pustules and leukocytosis. Patients receive 1 mg of dexamethasone every morning, clobetasol cream 0.05% twice daily, gentamycin 0.1% three times daily, and 3% salicylic acid cream, while to avoid the emergence of preeclampsia aspirin is given at a low dose of 75 mg/day, and we use vipalbumin to treat hypoalbuminemia. The patient gave birth to premature twins by normal delivery. Conclusion: GPPP is a rare dermatosis with serious risks and consequences for both mother and child. Supportive management is needed to maintain pregnancy and prevent complications.